Diseño de un plan de marketing para la compañía Grunseg Cía. Ltda. dedicada a la actividad de seguridad física y electrónica ubicada en el barrio Granda centeno en el distrito metropolitano de Quito - Escobar Toapanta, Walter Marcelo (2013)
The main objective of the present work is to design the marketing plan for Grunseg Cia. Ltda. for position its brand in the security market, driving the mix marketing variables and a quality service, increasing its number of clients, with this the company can obtain a better profitability. Grunseg Cia. Ltda. was legally established in 2007, which has offered the Quiteño market the services of physic and electronic security to companies, building, small business, families, etc.